You are on page 1of 2

Denition.

For z C we dene
cos z =
1
2
(e
iz
+ e
iz
); sin z =
1
2i
(e
iz
e
iz
); coshz =
1
2
(e
z
+ e
z
); sinhz =
1
2
(e
z
e
z
).
Remark In all of what follows we will make use of the fundamental identity
() e
z+w
= e
z
e
w
, z, w C.
Here is a proof of (*) in which we leave out the nontrivial justication of some of the steps. We have
e
z+w
=

n=0
(z + w)
n
n!
=

n=0

m=0
z
m
m!
w
nm
(n m)!

m=0

n=m
z
m
m!
w
nm
(n m)!

m=0

z
m
m!

n=m
w
nm
(n m)!

m=0

z
m
m!

n=0
w
n
n!

m=0
z
m
m!
e
w
= e
z
e
w
.
From the denitions we immediately deduce that
(1) e
iz
= cos z + i sinz
and that
(2) cos
2
z + sin
2
z = 1, cosh
2
z sinh
2
z = 1.
From (*) we obtain the addition formulae
(3) sin(z + w) = sinz cos w + cos z sinw, cos(z + w) = cos z cos w sinz sinw.
Dierentiating term by term the power series that dene the exponential function we nd that
(4)
d
dz
e
z
= e
z
.
One could also use (*) to deduce (4). For any constant a we have
d
dz
f(az) = af

(az) provided f is dieren-


tiable in the complex; this fact, (1) and the denitions immediately imply that
(5)
d
dz
cos z = sinz;
d
dz
sinz = cos z;
d
dz
coshz = sinh z;
d
dz
sinhz = cosh z.
1
We have
(6) e
iz
=

n=0
(iz)
n
n!
=

m=0
(iz)
2m
(2m)!
+

m=0
(iz)
2m+1
(2m + 1)!
=

m=0
(1)
m
z
2m
(2m)!
+ i

m=0
(1)
m
z
2m+1
(2m + 1)!
.
This gives
(7) e
iz
=

m=0
(1)
m
z
2m
(2m)!
i

m=0
(1)
m
z
2m+1
(2m + 1)!
.
Combining (6) and (7) we get
(8) cos z =

m=0
(1)
m
z
2m
(2m!)
, sinz =

m=0
(1)
m
z
2m+1
(2m + 1)!
.
We have
(10) e
z
=

n=0
z
n
n!
=

m=0
z
2m
(2m)!
+

m=0
z
2m+1
(2m + 1)!
.
This gives
(11) e
z
=

m=0
z
2m
(2m)!

m=0
z
2m+1
(2m + 1)!
.
Combining (10) and (11) we get
(12) cosh z =

m=0
z
2m
(2m)!
, sinhz =

m=0
z
2m+1
(2m + 1)!
.
If z = x + iy where x, y are real we have
(13)
cos z =
1
2

e
i(x+iy)
+ e
i(x+iy)

=
1
2

e
y+ix
+ e
yix

=
1
2

e
y
(cos x + i sinx) + e
y
(cos x i sinx)

=
1
2

cos x(e
y
+ e
y
) i sinx(e
y
e
y
)

= cos xcoshy i sinxsinhy.


Changing a sign and dividing by i in the third line of the preceding calculation one obtains
(14)
sinz =
1
2i

e
y
(cos x + i sinx) e
y
(cos x i sinx)

=
1
2i

i sinx(e
y
+ e
y
) sinx(e
y
e
y
)

= sinxcoshy + i cos xsinhy.


Finally,
(15) coshz = cos iz = cos(y + ix) = cos(y) coshx + sin(y) coshx = cosh xcos y coshxsiny
and
(16)
sinhz = i sin(iz) = i sin(y + ix) = i(sin(y) coshx + i cos(y) sinhx) = sinhxcos y + i coshxsiny.
Whew!
2

You might also like